Genotyping single nucleotide polymorphisms and inferring ploidy by amplicon sequencing for polyploid, ploidy‐variable organisms. (6th June 2021) - Delomas, Thomas A.; Willis, Stuart C.; Parker, Blaine L.; Miller, Donella; Anders, Paul; Schreier, Andrea; Narum, Shawn
Abstract: Whole genome duplication is hypothesized to have played a critical role in the evolution of several major taxa, including vertebrates, and while many lineages have rediploidized, some retain polyploid genomes. Additionally, variation in ploidy can occur naturally or be artificially induced within select plant and animal species. Modern genetic techniques have not been widely applied to polyploid or ploidy‐variable species, in part due to the difficulty of obtaining genotype data from polyploids. In this study, we demonstrate a strategy for developing an amplicon sequencing panel of single nucleotide polymorphisms for high‐throughput genotyping of polyploid organisms. We then develop a method to infer ploidy of individuals from amplicon sequencing data that is generalized to apply to any ploidy and does not require prior identification of heterozygous genotypes. Combining these two techniques will allow researchers to both infer ploidy and generate ploidy‐aware genotypes with the same amplicon sequencing panel. We demonstrate this approach with white sturgeon Acipenser transmontanus, a ploidy‐variable (octoploid, decaploid and dodecaploid) imperiled species under conservation management in the Pacific Northwest and obtained a panel of 325 loci. These loci were validated by examining inheritance in known‐cross families, and the ploidy inference method was validated with known ploidy samples. We provide scripts that adapt existing pipelines to genotype polyploids and an R package for application of the ploidy inference method. We expect that these techniques will empower studies of genetic variation and inheritance in polyploid organisms that vary in ploidy level, either naturally or as a result of artificial propagation practices.